Pirates of the Caribbean : On Stranger Tides - Cruz, Penelope; Depp, Johnny; Marshall, Rob.; McShane, Ian, 1942-; Rush, Geoffrey (Burbank, CA : Disney, 2011)
A tale of truth, betrayal, youth, demise, and mermaids! When Jack crosses paths with a woman from his past, he's not sure if it's love, or if she's a ruthless con artist using him to find the fabled Fountain of Youth. Forced aboard the ship of the most feared pirate ever, Jack doesn't know who to fear more, Blackbeard or the woman from his past.
2-disc Combo pack. Disc 1 - Blu-ray feature film + bonus. Disc 2 - DVD feature film + bonus.
Bonus features: bloopers of the Caribbean; LEGO(R) animated shorts: Captain Jack's brick tales.
Director, Rob Marshall.
Ian McShane, Penelope Cruz, Johnny Depp, Geoffrey Rush.
Rated: PG.
The Blu-ray disc can only be played on Blu-ray disc players and will not play on standard DVD players.
Keywords: Action for Conflict Transformation|xAdventure.; Fantasy; Debt -- Fiction; Man-woman relationships -- Fiction; Pirates -- Fiction; Action and adventure films; Comedy films; Fiction; Pirate films